تقييم معلومات السيدات حول لقاح فيروس الورم الحليمي البشري HPV - دونا عيسى (Latakia University Journal -Medical Sciences Series, 2019)
Human Papilloma Virus (HPV) is a common virus, which causes some of its very serious types of cervical cancer, which is often slow-growing and does not show symptoms in its early stages, According to World Health Organization statistics, cervical cancer is the second most common cancer in women living in less developed regions, which justifies the importance of spreading health awareness and culture about the causes of the disease, ways of infection, and increasing the level of knowledge about human papilloma virus, which is the main cause of the disease, And prevention methods by vaccinating girls at an early age with HPV vaccine as a preventive step against cervical cancer. The study aimed to assess the information of women about HPV vaccine. To achieve this, the researcher used the questionnaire method to collect data from a sample of 150 women in the Obstetric and Pediatric hospital in Lattakia. The questionnaire was divided into four sections: demographic variables, information level about cervical cancer, the level of information about HPV, and the level of information about the HPV vaccine. The data were analyzed using statistical tests, the most important of which are: One-Sample T. test, and One Way ANOVA. The researcher found several results, the most important are: More than a quarter of the sample have never heard of HPV virus and its vaccine. There is also an overall average assessment of the level of the women information about cervical cancer, and a low overall assessment of their level of knowledge about HPV and its virus, and the level of information is influenced by the studied demographic factors. The researcher recommends increasing attention to spreading awareness of prevention of cervical cancer in Syrian women, spreading the health culture that defines women with the causes of the disease, especially HPV, and the importance of vaccination to prevent it, and the need for continuous early detection to increase the chances of recovery if it exists. يعد فيروس الورم الحليمي البشري من الفيروسات الشائعة الانتشار، والتي تسبب بعض أنواعه الشديدة الخطورة سرطان عنق الرحم، الذي غالباً ما يكون بطيء النمو ولا تظهر له أعراض في مراحله المبكرة، ووفق إحصائيات منظمة الصحة العالمية فإن سرطان عنق الرحم ثاني أكثر السرطانات شيوعاً لدى النساء القاطنات في المناطق الأقل تقدماً، مما يبرر أهمية نشر التوعية والثقافة الصحية المتعلقة بمسببات هذا المرض، وطرق العدوى به، وزيادة مستوى المعرفة بفيروس الورم الحليمي البشري الذي يعد المسبب الرئيس لهذا المرض، ووسائل الوقاية منه والتي تتم من خلال تطعيم الفتيات في سن مبكرة بلقاح HPV كإجراء وقائي من الإصابة بسرطان عنق الرحم. وهدف البحث إلى تقييم معلومات السيدات حول اللقاح المضاد لفيروس الورم الحليمي البشري HPV، ولتحقيق ذلك استخدم الباحث أسلوب الاستبانة لجمع البيانات من عينة مكونة من 150 سيدة في مشفى التوليد والأطفال في مدينة اللاذقية، وتم تقسيم الاستبانة إلى أربعة أقسام تضم: المتغيرات الديموغرافية، مستوى المعلومات حول سرطان عنق الرحم، مستوى المعلومات حول فيروس الورم الحليمي البشري، ومستوى المعلومات حول لقاح HPV. وتمّ تحليل البيانات باستخدام اختبارات إحصائيّة أهمّها: اختبار الوسط الحسابي One- Sample T. test، واختبار التباين الأحادي One Way ANNOVA. وقد توصل الباحث إلى عدّة نتائج أهمّها: أكثر من ربع العينة لم يسمعن أبداً عن فيروس HPV ولقاحه. كما يوجد تقييم إجمالي متوسط لمستوى معلومات السيدات محل الدراسة حول سرطان عنق الرحم، وتقييم إجمالي ضعيف لمستوى معلوماتهن حول فيروس HPV ولقاحه، كما يتأثر مستوى المعلومات بالعوامل الديمغرافية المدروسة. ويوصي الباحث بزيادة الاهتمام بنشر الوعي الوقائي لمكافحة مرض سرطان عنق الرحم لدى السيدات السوريات، ونشر الثقافة الصحية التي تعرّف بمسببات هذا المرض ولاسيما فيروس الورم الحليمي البشري، وأهمية اللقاح للوقاية منه، وضرورة الكشف المستمر المبكر لزيادة فرص الشفاء في حال وجوده.